IMPLEMENTASI METODE PEMBELAJARAN DISKUSI KELOMPOK PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS X SEMESTER GENAP DI SMA NEGERI DARUSSHOLAH SINGOJURUH - Ahmad Izza Muttaqin; Riza Faishol; Bey Arifin Sidon; Yunia Humairoh (INCARE, International Journal of Educational Resources, 2021)
This study describes the implementation of the group discussion learning method in Islamic religious education learning for grade X even semester at SMA Negeri Darussholah Singojuruh in 2019/2020. The type of research used in this research is descriptive qualitative. Methods of data collection using non-participant observation methods, semistructured interviews, and documentation. Research subjects or respondents in the study were the principal, Islamic education teachers, students of class X MIA 7. The validity of the data was done by means of triangulation methods. And data analysis includes data collection (data collection), data reduction (data reduction), data display (data presentation), conclusion drawing / verification. The results of the study explained that PAI educators at SMA Negeri Darussholah Singojuruh, in planning the teaching process, the teachers prepared syllabus, Rpp, and subject matter. In the implementation of learning, educators have carried out in accordance with the steps of the group discussion method. And for evaluation / appraisal, educators do a written test and to improve their scores, they carry out a remedial process, and the evaluation is carried out in the middle of the semester and the end of the semester.